2017
DOI: 10.1080/1828051x.2017.1292830
|View full text |Cite
|
Sign up to set email alerts
|

Response of broiler chickens to dietary inclusion of fermented canola meal under heat stress condition

Abstract: Feeding high levels of canola meal to monogastric animal require reducing antinutritional factors such as glucosinolates and fibre. Solid state fermentation is known to reduce antinutritional factors and improve nutritional quality of feedstuffs. In this study, canola meal was treated with Lactobacillus salivarius in solid state fermentation for 30 days and included in diet with 4 levels of 0 (control), 10, 20, and 30%. From 29 to 35 days of age, equal number of birds from each dietary treatment was exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
(29 reference statements)
1
12
1
1
Order By: Relevance
“…The crude protein (CP) content in UCAM appear to slightly increase by 1.46% in ASCAM, 2.00% in AFCAM and 2.11% in COCAM. The margin of increase in CP content in the present study is lower compared to earlier reports which found 8.1% and 16.5% increase in CP content of canola meal fermented with food grade Aspergillus sojae and Aspergillus ficuum, respectively [11] and a 2.4% increase in CP content of canola meal fermented with Lactobacillus salivarius [13]. The initial crude fat content in UCAM (15.63%) also seem to decrease to 15.47% in ASCAM, 15.31% in COCAM and 15.18% in AFCAM.…”
Section: Proximate Compositioncontrasting
confidence: 96%
See 2 more Smart Citations
“…The crude protein (CP) content in UCAM appear to slightly increase by 1.46% in ASCAM, 2.00% in AFCAM and 2.11% in COCAM. The margin of increase in CP content in the present study is lower compared to earlier reports which found 8.1% and 16.5% increase in CP content of canola meal fermented with food grade Aspergillus sojae and Aspergillus ficuum, respectively [11] and a 2.4% increase in CP content of canola meal fermented with Lactobacillus salivarius [13]. The initial crude fat content in UCAM (15.63%) also seem to decrease to 15.47% in ASCAM, 15.31% in COCAM and 15.18% in AFCAM.…”
Section: Proximate Compositioncontrasting
confidence: 96%
“…There was a reduction (p < 0.05) in pH values from 6.07 (UCAM) to 6.03 (ASCAM), 5.87 (AFCAM) and 5.94 (COCAM), with AFCAM having the lowest pH value ( Table 2). This result agrees with the reports of other studies [11,13,16] which also observed reduction in the pH of canola meal fermented with Lactobacillus salivarius and CAM fermented with Saccharomyces cerevisiae. A decline in pH suggests increase in organic acids produced by the microorganisms during SSF [49] or breakdown of carbohydrates into organic acids [50].…”
Section: Ph Total Titratable Acidity and Colour Attributessupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, some antinutritional factors present in seaweed could interfere with the bioavailability of nutrients in diets and decrease the availability of nutrients in animals . Fermentation has been widely adopted to develop a novel functional feedstuffs for livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that the impact of rapeseed products, rich not only in NSP, lignin and polyphenols but also in glucosinolates, may be more pronounced in turkeys than in broiler chickens due to a much longer fattening period in the former [ 4 ]. According to many authors, the inclusion rates of rapeseed products in poultry diets should not exceed 15–20% to prevent metabolic disorders caused by glucosinolates and not to compromise the growth performance of birds [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%